2021
DOI: 10.1021/acsami.1c18038
|View full text |Cite
|
Sign up to set email alerts
|

Realizing Near-Unity Quantum Efficiency of Zero-Dimensional Antimony Halides through Metal Halide Structural Modulation

Abstract: Zero-dimensional (0D) organic metal halides have attracted significant attention because of their exceptional structure tunability and excellent optical characteristics. However, controllable synthesis of a desirable configuration of metal halide species in a rational way remains a formidable challenge, and how the unique crystal structures affect the photophysical properties are not yet well understood. Here, a reasonable metal halide structural modulation strategy is proposed to realize near-unity photolumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 27 publications
5
40
0
Order By: Relevance
“…Another critical bottleneck that restricts the practical applications of perovskites is the poor stability toward various chemical and physical factors including water, humid air, polar solvents, light, etc., due to the ionic nature of material itself. [ 27 ] As a result, the PL emission is easily quenched by these external stimuli along with the structural decomposition or phase transitions, especially perovskites without additional protection tend to hydrolyze under the corrosion of water vapor. [ 28–31 ] Additionally, the hydrolyzation of lead halide perovskite also brings about severe environmental pollution of Pb 2+ ion in the application process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another critical bottleneck that restricts the practical applications of perovskites is the poor stability toward various chemical and physical factors including water, humid air, polar solvents, light, etc., due to the ionic nature of material itself. [ 27 ] As a result, the PL emission is easily quenched by these external stimuli along with the structural decomposition or phase transitions, especially perovskites without additional protection tend to hydrolyze under the corrosion of water vapor. [ 28–31 ] Additionally, the hydrolyzation of lead halide perovskite also brings about severe environmental pollution of Pb 2+ ion in the application process.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26] Simultaneously considering the biological toxicity of Pb 2+ ion and lower PLQY of blue emitting perovskite, it is greatly significant and stringent to design lead-free 0D perovskites comprising environment-friendly metals as highly efficient blue emitters to achieve balanced development of three primary-color in high-definition display and lighting devices.Another critical bottleneck that restricts the practical applications of perovskites is the poor stability toward various chemical and physical factors including water, humid air, polar solvents, light, etc., due to the ionic nature of material itself. [27] As a result, the PL emission is easily quenched by these external stimuli along with the structural decomposition or phase transitions, especially perovskites without additional protection Despite remarkable luminescent performance of 0D lead halide perovskites, achieving highly efficient blue light emission is extremely challenging and crucial for this domain. Considering the high toxicity of Pb 2+ ion, it is significant to explore water-stable lead-free 0D halides as highly efficient and stable blue emitting materials.…”
mentioning
confidence: 99%
“…Although our estimated exciton binding energy would be comparable to that of 0D halides showing STE, the small S and large phonon frequency of the blue emission are distinct from other typical 0D perovskite halides showing STE, where a large S and small ℏω are reported. [79][80][81] Therefore, specifying the origin of the PL is not sufficient and it is still an open question. Detailed theoretical and experimental investigations on the origin of the PL emission would be useful in future work.…”
Section: Wwwadvopticalmatdementioning
confidence: 99%
“…Broad-band emissions originating from triplet STEs of Sb 3+ have been obtained in the region spanning from yellow to red by introducing Sb 3+ into 0D structured Cs 2 SnCl 6 and Cs 2 InCl 5 ·H 2 O, respectively, due to the strong electron–phonon couplings. 21–23 Furthermore, a red-shifted emission is observed on the Sb 3+ -doped organic–inorganic hybrid InCl 6 (C 4 H 10 SN) 4 ·Cl upon exposure to ethanol and N , N -dimethylformamide (DMF) vapor with the emission peak red shifted from 550 to 600 nm. 28 Thus, Sb 3+ doped in 0D perovskite crystals has shown great potential for application as a light emitter in multicolor displays, with excellent color tunability covering the entire visible spectra for promising luminescence centers.…”
Section: Introductionmentioning
confidence: 99%
“…Trivalent antimony Sb 3+ ions with an electronic configuration 5s 2 have been introduced into rare-earth phosphates and borates as optical activators and produce emission in the UV-blue region; however, the ultra-short emissive wavelength limits their practical application in display and lighting. [19][20][21][22] Very recently, it has been reported that Sb 3+ doping in leadfree halide perovskite crystals produces multicolor photoluminescence (PL) with high efficiency. [23][24][25][26][27][28] The PL of Sb 3+ in perovskites originates from triplet self-trapped excitons of Sb 3+ ions which are strongly sensitive to their coordination crystallographic environment.…”
Section: Introductionmentioning
confidence: 99%